Pengembangan Kapasitas Guru dalam Meningkatkan Kesejahteraan di SD Inpres 45 Ambon - Lisye Magdalena Liur; Teddy Christianto Leasiswal; Wiljan Atfentia Kotngoran; Altje Delaya Tamole (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The purpose of this community service activity is to enhance the capacity of teachers at SD Inpres 45 Ambon thru a workshop with the theme "Teacher Capacity Development in Improving Welfare." The focus of the workshop is to enhance teachers' soft skills. Intrapersonal and interpersonal skills, as well as the use of digital technology and financial literacy, are included in this category. To measure the participants' increased understanding, pre-tests and post-tests were used. The pre-test results showed that teachers had a poor understanding of finance and technology, although they were highly motivated. The post-workshop tests showed a significant improvement in understanding family financial planning and methods for increasing income with digital skills. Additionally, teachers were instructed to use applications like Google Classroom and Canva to enhance learning and open up additional business opportunities, such as private tutoring. This activity aligns with Jaenuri's (2017) opinion on the importance of building teachers' social skills and personality. Additionally, the findings of Yani and Fahmi (2022) indicate that interactive workshops are effective in improving teachers' abilities. This activity makes teachers more confident in managing their finances and seeing opportunities for additional well-being. Therefore, this service not only enhances teachers' professional capacity but also increases their income. This also provides an example that can be applied in other schools with similar situations.